Analysis of Operational Performance of Fishery Port Tanru Sampe Jeneponto, South Sulawesi - Idrus, Misliah; Chairunnisa, Andi Sitti; Djafar, Wihdat; Djalante, Abdul Haris; Fitriah, Rifkah; Sabir, Sabnur (International Journal of Metacentre, 2022)
The fishing port combines fishing activities at sea and distribution activities to consumer areas. The fishing port must guarantee the needs of ships that dock and land and ensure that the landed catch remains of good quality. The Tanru Sampe Fishing Port in Jeneponto Regency, South Sulawesi Province, is a type D Fish Landing Base (PPI) with a pier length of 45 m, a pool depth of around 0.5-4 m, an operating vessel capacity of 19-24 GT, and loading and unloading time of around 4 -5 hours. The condition of limited depth and long loading and unloading time causes the frequency of fishing to be less optimal. The research aims to analyze the port's performance using parameters based on the standards of the Director General of Capture Fisheries Number 20/KEP-DJPT/2015. The results of the study show that the performance of the port is generally of moderate value, with assessment parameters: 1) Administration and information of three variables, only one good variable, namely the availability of human resources, 2) Port facilities of six variables, only four variables have good value, namely the length of the pier, the depth of the pool, the completeness of marketing and distribution facilities, and the availability of portland. 3) Four out of nine variables for general services are good: mooring services, fishery production, frequency of ship visits, and ice distribution. n In investment and industry, there are three good variables: port land use and employment.